IMPACT OF DIGITALIZATION IN MANAGEMENT OF INTERNATIONAL BUSINESS IN ORGANIC AGRICULTURE. WAYS TO RESPOND TO CHALLENGES. USH PRO BUSINESS, INTER -BIO, WALLACHIA HUB STUDY CASE - Lianu, Costin; Rădulescu, Irina Gabriela; Dobre (Gudei), Simona Corina (Annals of Spiru Haret University. Economic Series, 2020)
Abstract Digital technologies are used in an increasingly in everyday life, in any aspects of human activities. Pandemics like Corona Virus imposed stricter rules for health and people, most probably, will prefer to be safer with organic products. Even before the crises, organic agriculture especially was on the path to digitalization. Now we realize better that Digitally Conducted Organic Agri-food (DCOA) solutions will emerge even faster. This paper is investigating the trends of evolution of digital transformation in organic agri-food industry and their impact on trade flows with food products. We look at the new emerging business models triggered by the DCOA solutions and the managerial challenges this will require especially for innovative start ups, farmers and SMEs in agri-food sector. Finally, we argue that university led innovation ecosystem, like the study case presented, may offer knowledge hubs for farmers, processors and sector branch organizations in the organic sector.